(untitled) (Journal of Engineering, 2023)
The need for renewable energy sources is higher than ever due to rising global warming, climate change, and ozone depletion. For refrigeration and air conditioning applications, adsorption refrigeration systems are viable alternatives cooling techniques. This study is a topic and part of the M.Sc. thesis. A field solar-powered ice maker unit was created, studied, tested, and evaluated on the 13th and 30th of May, 2022. Activated carbon and methanol pair was used to set up a refrigeration system in Baghdad (Al Dora). Experimental tests were carried out outdoors to determine the coefficient of performance COP and specific cooling power SCP of the system. The results showed that the lowest temperature obtained at the evaporative surface was (4 oC) and (3 oC) for the 13th and 30th of May, respectively, at the opening time of the valve between the evaporator and the generator at 9 pm. In addition, the amounts of methanol condensate were (0.340 kg) and (0.344 kg) for the 13th and 30th of May, respectively, while the maximum cycle coefficient of performance (COP) and specific cooling power SCP are about 0.57 and 0.14 kW/kga.c , respectively